2019
DOI: 10.1016/j.ecoenv.2019.01.085
|View full text |Cite
|
Sign up to set email alerts
|

High temperature aggravates the effects of pesticides in goldfish

Abstract: In human-altered rivers, fish are often conjointly exposed to an increase in water temperature due to global warming and to contamination by organic pollutants such as pesticides, but their combined effects are still elusive. Thermal and chemical stressors could potentially interact because high temperature increases metabolism and toxicant uptake, and can alter the ability of organisms to set up adequate stress responses and to maintain homeostasis. These combined stressors could thus potentially result in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 75 publications
1
31
0
1
Order By: Relevance
“…Other stressors such as climate change and water warming could also modulate the effects of pollutants, either through direct effects on the chemical properties of pollutants, and/or through complex interactive effects on neurophysiological pathways (Schiedek et al, 2007;Noyes et al, 2009). For instance, exposure to pesticides and water warming in goldfish had complex interactive effects on goldfish Carassius auratus proteome and cell integrity (Gandar et al, 2017b;Jacquin et al, 2019), and resulted in antagonistic effects on fish foraging activity in fish exposed to multiple stressors compared to fish exposed to single stressors (Gandar et al, 2015). To conclude, pollution effects often depend on the concomitant exposure to other biotic and abiotic stressors (Dinh Van et al, 2013Tüzün et al, 2015Tüzün et al, , 2017Debecker and Stoks, 2019;Saaristo et al, 2019), underlining the need for multistress approaches to better predict the cognitive and fitness consequences of pollution on wildlife.…”
Section: Multiple Stressor Effects On Behavior and Fitnessmentioning
confidence: 99%
“…Other stressors such as climate change and water warming could also modulate the effects of pollutants, either through direct effects on the chemical properties of pollutants, and/or through complex interactive effects on neurophysiological pathways (Schiedek et al, 2007;Noyes et al, 2009). For instance, exposure to pesticides and water warming in goldfish had complex interactive effects on goldfish Carassius auratus proteome and cell integrity (Gandar et al, 2017b;Jacquin et al, 2019), and resulted in antagonistic effects on fish foraging activity in fish exposed to multiple stressors compared to fish exposed to single stressors (Gandar et al, 2015). To conclude, pollution effects often depend on the concomitant exposure to other biotic and abiotic stressors (Dinh Van et al, 2013Tüzün et al, 2015Tüzün et al, , 2017Debecker and Stoks, 2019;Saaristo et al, 2019), underlining the need for multistress approaches to better predict the cognitive and fitness consequences of pollution on wildlife.…”
Section: Multiple Stressor Effects On Behavior and Fitnessmentioning
confidence: 99%
“…Liver lesions were quantified by standard histological techniques following previous studies in fish (Cuevas et al, 2016;Jacquin et al, 2019;van Dyk et al, 2007). Briefly, the liver was dissected, immediately fixed in 4% formalin, and then paraffin-embedded.…”
Section: Physiological Trait: Liver Lesionsmentioning
confidence: 99%
“…For each hepatic lesion, a score between 0 and 3 was associated according to the severity of the lesion. A global histopathological score reflecting the severity of the lesions was then calculated as the mean value of the different scores following previous studies (Jacquin et al, 2019).…”
Section: Physiological Trait: Liver Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, environmental factors such as temperature may alter the effects of toxicants on behavior. Jacquin et al [36] found that high temperatures aggravated the effects of pesticides in goldfish, and Lagesson et al [37] found that exposure to a hormonal growth promoter increased boldness behavior in mosquitofish, but that this increase depended on temperature. Araujo et al [38] observed that shrimps balanced exposure to contaminants with a sheltering behavior that protects individuals from predators; when confronted with a choice between a cleaner habitat with no shelter and a contaminated habitat with shelter, shrimps preferred the cleanest area, but when the uncontaminated area contained a predator signal, shrimps balanced the risk of predation and exposure to contamination by selecting a moderately contaminated area further away from predator signals, thereby increasing their exposure to the contaminant.…”
Section: Indirect Effects and Behaviormentioning
confidence: 99%